Resolvin D1 modulates the pulmonary immune response to agriculture dust exposure - Threatt, Alissa Nicole, author; Nordgren, Tara, advisor; Schaffer, Joshua, committee member; Schenkel, Alan, committee member (Colorado State University. Libraries, 2023)
Occupational exposure to agriculture dust causes a variety of acute and chronic pulmonary diseases including allergies, asthma, chronic obstructive pulmonary disease (COPD) and organic dust toxic syndrome (ODTS). These diseases have high impact on the healthcare system and limited treatments with variable efficacy. In addition, workers often display low compliance with required workplace personal protective equipment (PPE), increasing their risk for developing these diseases. Therefore, the development of new pharmacological interventions is critical to alleviate the burden on the healthcare system and improve the quality of life for patients who will inevitably develop occupational-related pulmonary diseases. Interleukin-22 (IL-22) is a cytokine in the anti-inflammatory interleukin-10 (IL-10) family of cytokines that has demonstrated a protective role in murine models of acute and chronic lung injury. It has been described as being exclusively produced by lymphocytes, however methodological limitations of the primary cited study restricted the exploration of other cell types as producers of IL-22. Upregulation of this cytokine by pharmacological means could prove beneficial for delaying the progression of occupational chronic pulmonary diseases. Omega-3 fatty acids and their metabolites have well-documented anti-inflammatory and pro-resolution functions in chronic pulmonary diseases and have been implicated in the induction of IL-22. Omega-3 fatty acids have shown overwhelming evidence in being anti-inflammatory by their function as substrates for the production of specialized pro-resolving mediators (SPMs), lipid metabolites that signal immune cells to transition to a resolution and repair state following inflammation. Resolvin D1 (RvD1), a metabolite of the omega-3 fatty acid docosahexaenoic acid (DHA), has shown to have anti-inflammatory and protective functions in a murine acute lung injury model. To evaluate the source of IL-22 in the pulmonary response to agricultural dust, mouse alveolar macrophages were co-exposed to 1% hog dust extract (DE) collected from swine confinement facilities in the Midwest US and treated with either 10 nM or 100 nM RvD1. Cells were incubated for up to 24 hours, supernate was collected at the desired timepoint, and enzyme-linked immunosorbent assays (ELISAs) were performed to assess protein expression. Cells were also lysed to determine intracellular IL-22 protein concentrations. Cells exposed to DE exhibited increased pro-inflammatory cytokines interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) as well as increased IL-10 and IL-22 production, demonstrating macrophages as a source of IL-22 in the immune response to organic dust. Cells exposed to DE and treated with RvD1 demonstrated significant decreases in IL-6 and TNF-α and increases in IL-10. To determine the efficacy of RvD1 as an inducer of IL-22, and as a potential treatment for organic dust-induced lung injury, C57BL/6 (WT) and full-body IL-22 knock-out (KO) mice were intranasally instilled (IN) with 12.5% DE 5 days/week for 3 weeks and injected intraperitoneally (IP) with 250 ng RvD1 once per week. Animals were allowed to recover for 5 hours or 3 days before sacrifice where bronchoalveolar lavage fluid (BALF) was collected for cytokine and cellular infiltrate evaluation to determine the role of RvD1 in the reduction of the immune response to organic dust exposure. BALF cytokines exhibited significant increases in the production of IL-10 in KO mice exposed to DE and treated with RvD1 with a 3-day recovery. Cellular infiltrates demonstrated decreased neutrophil infiltration and increased lymphocyte recruitment in KO mice exposed to DE after a 3-day recovery and further significant decreases in mice treated with RvD1 with a 3 day recovery. The data support the production of IL-22 by alveolar macrophages and its induction by RvD1. They also demonstrate the effects of RvD1 on the pulmonary immune response to agriculture dust and as a potential therapeutic for organic dust-induced chronic pulmonary diseases.
Keywords: lung inflammation; organic dust; specialized pro-resolving mediators; macrophage; IL-22; Resolvin D1